Anti-imperialist modernism : race and transnational radical culture from the Great Depression to the Cold War - Balthaser, Benjamin (Class, culture., 2016)
Anti-Imperialist Modernism excavates how U.S. cross-border, multi-ethnic anti-imperialist movements at mid-century shaped what we understand as cultural modernism and the historical period of the Great Depression. The book demonstrates how U.S. multiethnic cultural movements, located in political parties, small journals, labor unions, and struggles for racial liberation, helped construct a common sense of international solidarity that critiqued ideas of nationalism and essentialized racial identity. The book thus moves beyond accounts that have tended to view the prewar "Popular Front" through tropes of national belonging or an abandonment of the cosmopolitanism of previous decades. Impressive archival research brings to light the ways in which a transnational vision of modernism and modernity was fashioned through anticolonial networks of North/South solidarity.